ANALYSIS OF THE INFLUENCE OF LOCATION, PROMOTION AND HEALTH OFFICERS IN INFLUENCING DECISION ON SELECTION OF FIRST LEVEL HEALTH FACILITIES (FKTP) PARTICIPANTS OF BPJS HEALTH IN ADVANCED MEDICAL CENTER - Ekawati, Ekawati; Mulyowahyudi, Alugoro (Dinasti Publisher, 2021)
This study aims to analyze the influence of location, promotion and health workers in influencing the decision to choose a First Level health facility (FKTP) for BPJS Kesehatan participants at the Advanced Medical Center. This research is quantitative. The population in the study were BPJS patients who were registered at the Advanced Medical Center. The sampling technique used accidental sampling with a sample size of 100 people. The research data were analyzed using multiple linear regression. The results of the t-test for the variables of location, promotion and health care workers were significant for the decision on choosing health facilities at the Advanced Medical Center. Suggestions for further research are to include other factors that have a strong influence on health facility selection decisions.